Case Report: Successful immune checkpoint inhibitor rechallenge after sintilimab-induced Guillain-Barré syndrome - Ye, Lin; Yue, Wan Rong; Shi, Hao; Li, Jian Ren; Qun, Yu Ya (Frontiers in Immunology, 2025)
Immune checkpoint inhibitors (ICIs) have revolutionized hepatocellular carcinoma (HCC) treatment, while immune-related adverse events (IRAEs) pose significant challenges. We report a 60-year-old male with unresectable HCC who developed Guillain-Barré syndrome (GBS), a rare but severe neurologic complication, after three cycles of sintilimab plus bevacizumab biosimilar and conventional transarterial chemoembolization (c-TACE). The patient presented with progressive ascending weakness, reaching symmetric quadriparesis with proximal muscle strength of 2/5 in upper limbs and 1/5 in lower limbs. Following sintilimab discontinuation, treatment with intravenous immunoglobulin (2 g/kg) and oral prednisone (30 mg/day) achieved complete neurological recovery within one month. Given the patient’s favorable initial tumor response and strong request, immunotherapy was cautiously reinstated using tislelizumab after thorough clinical evaluation. Following four cycles of treatment, significant tumor response enabled successful conversion surgery with major pathological response (necrosis rate >70%). With 26-month survival and no evidence of recurrence, this case demonstrates the potential feasibility of ICI rechallenge with an alternative PD-1 inhibitor following sintilimab-induced GBS. Our experience suggests that ICI-related neurological adverse events may be drug-specific rather than class-specific, potentially providing valuable treatment options for patients showing favorable tumor response despite experiencing severe IRAEs, though larger studies are needed for validation.